Efektivitas Pembuatan Surat Perintah Tugas Melalui Aplikasi SIPENO di Biro Umum Kantor Sekretariat Daerah Provinsi Jawa Timur - Wika, Adevansyah; Priambodo, Bayu (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2024)
This research discusses the effectiveness of creating Task Assignment Letters through the SIPENO Application at the office of the Regional Secretariat of East Java Province. The aim of this study is to determine how successful the SIPENO application is in generating Task Assignment Letters. This research utilizes effectiveness theory as proposed by Budiani. There are four indicators used to measure effectiveness in this study: target accuracy, program socialization, program objectives, and program monitoring. The method employed in this research is descriptive qualitative. Data collection was conducted through direct observation, interviews with employees who use the SIPENO application, documentation on the use of the SIPENO application, and data compilation. The results of this study show that the four important indicators in using the SIPENO application for creating Task Assignment Letters target accuracy, program socialization, program objectives, and program monitoring can run quite effectively and are in line with the goals of implementing the SIPENO application. However, improvements to the SIPENO application are still needed to facilitate easier creation of Task Assignment Letters.